E-presence in measuring employee performance in the implementation of national road region IV West Java Province ministry of public works and public housing - Tondang, Berlianta; Istambul, Muhammad Rozahi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
Employee attendance is an important factor in ensuring that an agency or company meets its objectives; it is related to discipline and has an impact on the performance of each employee. As a result, there is a need to collect special data to record attendance and absences so that professional activities can be recorded in real time and measured. There are a number of ways to build a good attendance information system, one of which is the use of information technology, where its application is to the Regional Office IV of National Roads Implementation of West Java Province, In other words, the system used in the attendance process still uses fingerprints when used by gluing each employee's finger on the screen. A certain tool One of the concerns of employees during the Covid-19 transmission period at that time, where the implementation of the attendance would result in the touch of one finger to the other, and this was indicated to cause Covid-19 transmission. Based on the above problems and to support the government's recovery and prevention of covid-19 transmission, a web-based attendance application was created, namely the PUPR e-Presence.